Identification of skiing techniques with a single inertial sensor on the back: preliminary methodological approaches - Petrone, N.; Marcolin, G.; Cognolato, M.; Conte, D.; Jahnel, R.; Pfusterschmied, J.; Rieder, R.; Müller, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
MEMS have become a very important technology in sport science. In alpine ski racing inertial sensors are a promising tool to simplify kinematic analyses without using a huge amount of equipment (Brodie et al. 2008). But also for injury prevention these systems can play an important role to detect threatening falls on the earliest possible moment (Huber et al. 2012). Additional a recently developed airbag for professional skiers will be adopted at the forthcoming Olympics winter games. Aim of this study was to introduce a classification of the skill technique of recreational skiers by means of inertial sensors: this will contribute to the development or optimization of future algorithms for airbags dedicated to these skiers.